2002
DOI: 10.1002/jmv.2167
|View full text |Cite
|
Sign up to set email alerts
|

Lack of susceptibility of Chacma baboons (Papio ursinus orientalis) to hepatitis C virus infection

Abstract: The main reason to ascertain whether baboons are susceptible to infection with hepatitis C virus (HCV) is the need to replace chimpanzees, which are endangered, as an animal model for undertaking research into the biology and host-virus interactions of HCV, and for developing a vaccine against this virus. A second reason is that baboons are a possible source of xenografts for human liver transplantation. We inoculated serum containing HCV into four Chacma baboons and monitored them for 52 weeks for evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Baboons are phylogenetically close to humans, have four immunoglobulin G (IgG) subclasses, and possess cross-reactive Ig and cluster of differentiation antigens similar to those of humans and chimpanzees (16). The overall profile of baboons, as a less costly nonendangered species, more accessible animal model, and yet possessing immunology comparable to that of humans and chimpanzees, makes them a suitable animal model for preclinical studies of vaccine, although they are not susceptible to HCV infection (34).…”
mentioning
confidence: 99%
“…Baboons are phylogenetically close to humans, have four immunoglobulin G (IgG) subclasses, and possess cross-reactive Ig and cluster of differentiation antigens similar to those of humans and chimpanzees (16). The overall profile of baboons, as a less costly nonendangered species, more accessible animal model, and yet possessing immunology comparable to that of humans and chimpanzees, makes them a suitable animal model for preclinical studies of vaccine, although they are not susceptible to HCV infection (34).…”
mentioning
confidence: 99%
“…Chimpanzees are the only non-human primates known to be susceptible to HCV infection and have proved a useful model for studying viral biology. Conversely, baboons (Papio genus) are phylogenetically close to humans, have reasonably large livers, are not endangered and are not infected by HCV [50]. As such, these organs represent one potentially attractive source of organs in the future.…”
Section: Alternative Sources For Donor Graftsmentioning
confidence: 97%
“…Baboon livers have been transplanted into humans on several occasions with recipient survivals on the order of hours to months [51][52][53]. More sophisticated, recent studies using large numbers of baboons, multiple HCV genotypes and very sensitive detection techniques have shown that chacma baboons were not susceptible to HCV infection and, thus, could serve as a source of xenografts for HCV-infected individuals [50]. A disadvantage of using primates is the inability at present to genetically manipulate these donors.…”
Section: Alternative Sources For Donor Graftsmentioning
confidence: 99%
“…In search of alternative, more readily accessible experimental models for HCV numerous species have been tested for their susceptibility to HCV. Woodchucks, old- and new world monkeys, including Cynomolgus, Rhesus, Japanese, Green monkeys, Doguera (Abe et al, 1993), Chacma Baboons (Sithebe et al, 2002), Cottontop tamarins (Garson et al, 1997) and marmosets appear to be mostly resistant to HCV infection. Surprisingly, tree shrews ( Tupaia belangeri ) which are distantly related to primates (Schmitz et al, 2000; Xu et al, 2012) appear to support HCV infection to some level (Xie et al, 1998; Xu et al, 2007) (table I) and were recently shown to develop signs of severe liver disease, including steatosis, fibrosis and cirrhosis (Amako et al, 2010).…”
Section: Hcv Infection In Other Primate Speciesmentioning
confidence: 99%